Usability Evaluation And User Acceptance Testing (Uat) On Website-Based Digital Psychology Testing Application: A Case Study Of Psikotestyuk.Id - Adi Putra Dwi Nugraha; Wawan Laksito Yuly Saptomo (Jurnal Media Computer Science, 2026)
Digital transformation in the recruitment process through digital psychological testing applications such as psikotestyuk.id aims to increase the efficiency and objectivity of candidate selection. However, the effectiveness of this system is highly dependent on the ease of use and functional acceptance by end users, both prospective employees and HR. This study aims to evaluate the level of usability and user acceptance of the psikotestyuk.id application to identify operational obstacles and areas for system architecture improvement. The method used is Mixed Methods, integrating quantitative data from Usability Testing on 30 prospective employee respondents, and qualitative data from User Acceptance Testing (UAT) with in-depth interviews with three HR staff. The results showed an average usability score in the "Very Good" category with a value range of 4.21 to 4.40. Although functionally the system was very well received, UAT testing revealed the need for server infrastructure optimization to handle high traffic and the addition of a bulk data import feature to improve the efficiency of mass recruitment administration. In conclusion, the psikotestyuk.id application is very suitable for continued use with several development notes on the data scalability side.